Determination of critical gap for motorcycle at merging points of exclusive motorcycle lane in Malaysia - Mohamad Khaidir, Norfaizah (2018)
Although definitely not the worst in the region, Malaysia is facing a similar worrying situation as the countries in Southeast Asia which is a high number of motorcyclist fatalities. Various efforts have been implemented to improve this mortality rate and among the efforts that have contributed a large positive impact is the construction of exclusive motorcycle lanes (EMCL) aimed at segregating motorcycles from other motorised vehicles. Despite the huge growth in the EMCL demand, to date, the total length of EMCL constructed on primary roads in Malaysia are not more than 1% from the overall road length. One of the reason for the slow implementation of EMCL is the high construction cost. Therefore, an optimal design with sufficient capacity to cater for the traffic demand and at the same time cost effective must be developed. Capacity is one of the main parameters for optimal design of EMCL. Under-estimation of capacity at the design stage may result in a detrimental degree of congestion and over-estimation of capacity may cause the over-design of infrastructure that would in turn cause excessive investment. The capacity for the entire road network is also highly dependent on the estimated capacity value at access points where significant volumes of vehicle joining or leaving at access will cause interruption and capacity reduction to the overall traffic flow on the road network. On EMCL, access points are provided through egress (section to exit from the EMCL) and ingress (section for entering into EMCL). For accurate capacity estimation at interruption facilities like egress and ingress, the critical gap parameter is of high interest. Despite the suggested value of critical gap in international road design manuals, the critical gap value for motorcycle facilities remains as the missing link. As motorcycles are small in size compared with other motorised vehicles, the critical gap value for motorcycles is predicted to be smaller. Hence, the determination of critical gap for motorcycles at egress and ingress of EMCL forms the main interest of this study. Field data collection was conducted involving mainly videotaping the accepted and rejected gaps size and gap acceptance decision based on the oncoming vehicle type on the major road traffic by a single motorcycle from the minor road. The critical gap values obtained at egress are 2.28 seconds and 2.42 seconds when the oncoming vehicle is a passenger car and a heavy vehicle respectively and the critical gap value obtained at ingress where the traffic is made up of motorcycles only is 2.43 seconds. Findings from this study suggested that the critical gap for motorcyclists at egress and ingress is starkly lower than the recommended threshold value (6.2 seconds) used for other motorised vehicles at stop-controlled intersection. Applying a motorcycle’s critical gap for the estimation of capacity at the design stage of EMCL will directly affect the amount of space required to build EMCL, translating into more effective construction cost. This in turn, provides positive evidence to encourage the construction of more EMCL and in long term can possibly contribute for better road safety level in Malaysia.